Strengthening Russia's Fiscal Framework - Zakharova, Daria (IMF Working Papers; Working Paper ;, 2012)
Though many aspects of Russia's fiscal policy framework are close to best practice on paper, actual practice in recent years has been moving away from best practice. In particular, the continued focus on the overall rather than the nonoil balance, and the regular use of supplemental budgets to spend windfall oil revenues contribute to procylicality of fiscal policy, risking costly boom-bust cycles. Against this background, this paper suggests several improvements to the framework for fiscal policy.